Coevolution of Law and Science: A Clean Water Act Case Study - Adler, Robert W. (Columbia Journal of Environmental Law, 2019)
Despite recent political attacks, science is integral to environmental law and other regulatory regimes that are informed by new scientific research. It is inaccurate, however, to view the relationship between law and science as static. Traditionally, science is either seen as a servant of the legal system, responding to and supporting the applicable statutes and regulations; or we expect the legal system to respond or “catch up” to scientific advances. A more useful model, borrowed from evolutionary biology, is coevolution, an ongoing process in which law and science interact over time in an iterative process. A case study from the Clean Water Act (“CWA”) biocriteria program illustrates this dynamic process and suggests ways in which law and science can interact more effectively in the CWA and other regulatory regimes. It also highlights the conceptual difference between “scientific knowledge” and “regulatory knowledge,” and the importance of that distinction for separation of powers and democratic governance in the administration and enforcement of complex regulatory statutes.